Job application intention and search behavior of crowd workers / Zuria Saad ... [et al.] - Saad, Zuria; Fauzi, Muhammad Ashraf; Osman, Azim Azuan; Ramli, Mohd Safwan (Universiti Teknologi MARA Selangor, 2024)
This study aims to explore the job application intentions and search behaviors of crowd workers on online crowdsourcing platforms through the lens of Signaling Theory. The research involved 66 students from the Bachelor of Office System Management program at Universiti Teknologi MARA, Pahang, who participated as part-time crowd workers on various online platforms as part of the study requirements. The findings reveal significant positive relationships between job characteristics, person-job fit (as the signaler), and job-related factors influencing crowd workers' intentions and search behaviors (as the receivers), in alignment with Signaling Theory. These results provide a deeper understanding of crowd worker behavior, offering valuable insights for crowdsourcing platforms and job providers to enhance platform features and improve terms and conditions, ultimately making the platforms more attractive and efficient for both workers and employers.